Self-massage: a way to improve the health of people living with HIV/AIDS - Yudismil Babastro-Reinosa (Universidad de Guantánamo, 2013)
Since early HIV infection, antiretroviral therapy has been one of the fundamental objects of researchers to gain control of the infection. Medications are used to control the replication of the virus and stop the progression of the disease, the recommended combination of three or more drugs in a regimen called highly active antiretroviral therapy, it does not cure HIV infection, but people taking these drugs may decrease to undetectable levels in a blood sample, viral replication and reconstitute the immune system, improving their quality of life. Have shown that the most effective regimens remain some disadvantages, consequently resulting in unpleasant side effects (drug toxicity) sometimes inevitable. To reduce this situation to some extent natural medicine and traditional Chinese provides us with an element of one form of self-massage treatment. In our country there is widespread knowledge.